A thousand ways to say 'Delicious!'—Categorizing expressions of deliciousness from restaurant reviews on the social network site Yelp. (1st September 2016) - Ariyasriwatana, Weranuj; Quiroga, Luz Marina
Abstract: This study explored expressions of deliciousness—one of the main reasons people make specific food choices over others—from restaurant reviews on Yelp, a popular social network site. Through qualitative content analysis of 205 reviews from 41 food establishments in Hawaii, we found 8 main categories of expressions of deliciousness. These eight main categories created by both concept-driven and data-driven strategies are Sense, Culinary Affair, Matter of Heart, Health, Testimonial and Endorsement, Personal Signature, Consumer, and Restaurant. Each main category was further subcategorized. This meaningful categorization might contribute to healthier eating by helping policy makers and food companies craft effective strategies for healthy eating schemes, healthy menu items, or healthy food products. Marketers of any food product can also increase their market share by utilizing these categories, subcategories, and their underlying concepts in the planning stage. Detailed examples of nudging and social marketing campaigns inspired by our findings were provided. Moreover, social network sites can better serve health conscious and hedonic consumers by personalization through improved algorithms inspired by these categories.